2014
DOI: 10.1590/1809-4503201400020021
|View full text |Cite
|
Sign up to set email alerts
|

Saúde bucal no EpiFloripa: estudo prospectivo das condições de saúde de adultos de Florianópolis, Sul do Brasil

Abstract: Resumo: Objetivo: Descrever a metodologia e desafios de estudos de saúde bucal, inseridos em uma coorte prospectiva de adultos. Métodos: Foi obtida uma amostra de 2.016 adultos residentes em Florianópolis em 2009. Visitas domiciliares foram realizadas para a aplicação de um questionário sobre condições socioeconômicas e demográficas, de saúde geral, uso de serviços e de medicamentos, doação de sangue, violência doméstica e uma seção relativa à saúde da mulher. Informações sobre saúde bucal incluíram autoavalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…1). All these participants were contacted in two subsequent waves, and data were obtained from 1,222 adults in 2012 and 834 participants in 2014 13 …”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…1). All these participants were contacted in two subsequent waves, and data were obtained from 1,222 adults in 2012 and 834 participants in 2014 13 …”
Section: Methodsmentioning
confidence: 99%
“…Amputees, bedridden individuals, unable to stay in the proper position for anthropometric assessment, unable to answer the questionnaire for mental impairment, pregnant women or within 6 months postpartum were excluded. Further details about the study can be found elsewhere 12–14 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations